Social Media As The Arena Of Contemporary Politics: A Literature Review Of Gen Z And Millennial Candidate Strategies For The 2024 Elections - lianda, febi dwi; Ananda, Azwar (JUPE : Jurnal Pendidikan Mandala, 2025)
The development of digital technology, particularly social media, has brought significant changes to Indonesia's political landscape. The 2024 election is a pivotal moment where Generation Z and Millennials are increasingly dominating the political space, with social media as the main arena for their campaigns. This research aims to analyze the strategies used by legislative candidates from both generations in utilizing social media to attract voters' attention. Through a literature review approach, this research identifies various methods and tactics applied by young candidates, including content personalization, visual storytelling, as well as the use of issues relevant to the interests of young voters, such as climate change, gender equality, and education. Social media allows candidates to engage more directly and interactively with voters, reducing reliance on more formal, traditional campaign channels. However, challenges such as disinformation, opinion manipulation, and unequal digital access have also emerged as issues in these digital campaigns. In addition, this research also highlights the importance of digital literacy for candidates and voters, in order to optimize the potential of social media wisely and effectively. In addition, this research also highlights the importance of digital literacy for candidates and voters, in order to optimize the potential of social media wisely and effectively. Overall, social media serves as a tool that strengthens the political engagement of young voters, but also requires regulation and supervision to avoid negative impacts that can undermine the quality of democracy.